High density European Rail Traffic Management System (HD-ERTMS) for urban railway nodes: The case study of Rome. (March 2021) - Cuppi, Federico; Vignali, Valeria; Lantieri, Claudio; Rapagnà, Luca; Dimola, Nicola; Galasso, Tomaso
Abstract: The ERTMS (European Rail Traffic Management System) system has been created to standardize the European railway signals and to improve the performance of the railway network. Nowadays the growing rail traffic demand has carried to the congestion of the railway nodes, which turn out to be the bottle necks of the railway infrastructure. The High-Density European Traffic Management System (HD-ERTMS) has been developed as a solution to resolve this problem because, being perfectly superimposable to the Italian national signalling system, it can be applied without changing the current infrastructure. This paper describes the benefit that it will possible to reach by introducing this new signalling system analyzing the case study of the railway node of Rome.